The Anticancer Potential of Ethanol and Aqueous Extracts of Pluchea indica L. Leaves Against the WiDr Colorectal Cancer Cell Line - Nur Habibah; Ni Nyoman Astika Dewi; Luh Ade Wilan Krisna; Gusti Ayu Made Ratih (Jurnal Tumbuhan Obat Indonesia, 2025)
Colorectal cancer represents the second leading cause of cancer-related mortality worldwide and ranks asthe third most common cancer among both men and women. P. indica L. has demonstrated significantanticancer potential, attributed to its bioactive constituents, including phenolic and flavonoid compounds.Solvent type significantly influences extract quality and quantity, directly affecting pharmacological activity.This study aimed to evaluate the anticancer activity of ethanol and aqueous extracts from P. indica L. leavesin vitro, against the WiDr colorectal cancer cell line. Anticancer effects and IC50 values were determined bymeasuring cytotoxicity using the MTT assay. Results showed that both ethanol and aqueous extractsexhibited anticancer potential against the WiDr cell line. The ethanol extract exhibited higher cytotoxicity,as evidenced by reduced cancer cell viability (IC₅₀ of 21.82μg/mL±3.53), and was classified as active. Theaqueous extract had an IC₅₀ of 1,591.58μg/mL±272.8 and was classified as inactive. In conclusion, theethanol extract of P. indica L. showed greater potential for development as an anticancer agent againstcolorectal cancer. Keywords: Anticancer, Colorectal_cancer, Extract, Pluchea indica L., WiDr